PERAN DAN TANGGUNG JAWAB NOTARIS DALAM MEMBERIKAN PENYULUHAN HUKUM KEPADA CALON KLIEN TERKAIT PEMBUATAN AKTA (CONTOH KASUS: PUTUSAN NOMOR 200/PDT.G/2012/PN.JKT.SEL.) - Boy Nurdin; Stephanie Lorenza (Faculty of Law - Tarumanagara University, 2019)
The growth of people which impacted the social life causes many events and legal actions, therefore peoples make agreements stated in deed. However, a few of them does not clearly understand what kind of deed to be made. That raises some issues, how important is the role of the notarynin providing legalncounseling to prospective clientss in making the deed? And what about the notary responsible in providing legallcounseling to prospectivenclients? Thee Author examined the issues by normative juridicalnresearch method. Notaries has a very important role to provide information related to the deed thus it can be madenin accordance withnapplicable law, and the parties can feel safe and comfortable when implementing thenagreement, and the partiies understand the contents off the deed signed by them, because based on Article 13388 of the Indonesian CivilnCode states that “Allnlegally executed agreementssshall bind the individuals who havenconcluded them by law. They cannotnbe revoked otherwisenthan by mutualvagreement, or pursuant to reasonsnwhich are legallyndeclared to bensufficient. Theey shall benexecuted in goodd faith.” A notary can be considered guilty if the notary on purpose does not provide legal counseling to parties who do not know the law in terms of the deed to be made, then the nnotary must benresponsible for thendeed he made. Thus, the sanction for the notary concerned is that the notary may become a defendant in relevant cases.